2011
DOI: 10.1074/mcp.m111.010462
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide Characterization of miR-34a Induced Changes in Protein and mRNA Expression by a Combined Pulsed SILAC and Microarray Analysis

Abstract: The gene encoding the miR-34a microRNA is a transcriptional target of the p53 tumor suppressor protein and subject to epigenetic inactivation in colorectal cancer and numerous other tumor types. Here, we combined pulsed SILAC (pSILAC) and microarray analyses to identify miR34a-induced changes in protein and mRNA expression. pSILAC allowed to quantify the de novo protein synthesis of 1206 proteins after activation of a conditional miR-34a allele in a colorectal cancer cell line. ϳ19% of the detected proteins we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
149
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 186 publications
(159 citation statements)
references
References 68 publications
9
149
0
1
Order By: Relevance
“…Results represent the average ± SD (n=3). downregulation of SNAIL by miR-34, further indirect inhibition of SNAIL functions may be mediated by the downregulation of HDAC1 by miR-34a, which we have recently described, 14 since HDAC1 functions as a co-repressor of SNAIL. 26 Interestingly, pancreatic acinar cells with deletion of p53, which, therefore, presumably also express low levels of miR-34a and miR-34b/c, express high levels of SNAIL, SLUG, TWIST and ZEB1/2, show increased stemness markers and undergo EMT upon subculture.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Results represent the average ± SD (n=3). downregulation of SNAIL by miR-34, further indirect inhibition of SNAIL functions may be mediated by the downregulation of HDAC1 by miR-34a, which we have recently described, 14 since HDAC1 functions as a co-repressor of SNAIL. 26 Interestingly, pancreatic acinar cells with deletion of p53, which, therefore, presumably also express low levels of miR-34a and miR-34b/c, express high levels of SNAIL, SLUG, TWIST and ZEB1/2, show increased stemness markers and undergo EMT upon subculture.…”
Section: Discussionmentioning
confidence: 76%
“…Recently, we identified additional miR-34a targets, such as AXL, LDH1, MTA2 and LEF1, using a combined proteomic and transcriptomic approach. 14 MiRNAs regulate their targets via association of a ~7 nucleotide stretch, the so-called seed sequence, located in their 5' portion with a complementary sequence in the 3'-UTR of the target mRNA. 15,16 Additional base pairing may occur via nucleotides in the middle and 3' portion of the miRNA.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, miR-34a is a transcriptional target of p53, suggesting a positive feedback loop between p53 and miR-34a through SIRT1-dependent regulation (103). Notably, another study reported that HDAC1 also exhibits a robust decrease in protein levels following the induction of miR-34a in CRC cells (104). In a previous study evaluating the role of miRNAs in the antitumour action of calcitriol, miRNA expression profiles were examined in colon cancer cells treated with calcitriol (105).…”
Section: Mirna Regulatory Effects On Epigenetic Machinery In Crcmentioning
confidence: 99%
“…Current views on cancer cell mutations hold that there are two different types: driver mutations, which are behind cancer growth because they give tumor cells a growth advantage, and passenger mutations, which are just along for the ride. It has been suggested that ACSL4 overexpression is led by a driver mutation [18,34]; however, as it is capable per se of changing cancer cell phenotypes, ACSL4 overexpression may be thought of as a backseat driver factor which generates changes in gene expression and signaling pathways toward a highly aggressive phenotype, and which acts in addition to passenger mutations when the driver gene is mutated. In summary, this study derives an ACSL4 overexpression gene and functional proteomic signature which might reveal important information about novel mediators of breast cancer cell aggressiveness.…”
Section: Signal Transduction Pathways Triggered By Acsl4 Overexpressionmentioning
confidence: 99%